2011
DOI: 10.1128/aem.05392-11
|View full text |Cite
|
Sign up to set email alerts
|

Microcolony Formation by Single-Cell Synechococcus Strains as a Fast Response to UV Radiation

Abstract: UV radiation (UVR) has different effects on prokaryotic cells, such as, for instance, filamentation and aggregation in bacteria. Here we studied the effect of UVR on microcolony formation in two freshwater ). The cultures were exposed for 6 days to treatments with UVR or without UVR. PE-rich Synechococcus acclimated to LL had a low carotenoid/chlorophyll a (car/chl) ratio but responded faster to UVR treatment, producing the highest percentages of microcolonies and of cells in microcolonies. Conversely, the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…[11]. Another consideration is the recent finding that freshwater Synechococcus strains have been shown to respond rapidly to UV radiation with the formation of microcolonies [62]. If this is occurring in the marine environment then the resulting size of the microcolonies might be large enough to warrant the use of MAAs as sunscreen compounds and counter the argument that MAAs cannot be theoretically present in these small cells.…”
Section: Discussionmentioning
confidence: 97%
“…[11]. Another consideration is the recent finding that freshwater Synechococcus strains have been shown to respond rapidly to UV radiation with the formation of microcolonies [62]. If this is occurring in the marine environment then the resulting size of the microcolonies might be large enough to warrant the use of MAAs as sunscreen compounds and counter the argument that MAAs cannot be theoretically present in these small cells.…”
Section: Discussionmentioning
confidence: 97%
“…Microcystis elabens is a colonial form now reclassified as a species of Aphanothece in the same family as Synechococcus (Komárek & Anagnostidis, ; Vincent et al ., ) included in group A. It is interesting to note that one of the new strains of the enlarged group A (Lake Albano) is a single‐cell Synechococcus, which showed the tendency towards microcolony formation under ultraviolet radiation in laboratory experiments (Callieri et al ., ). This capability was not evident in other strains selected from other phylogenetic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that form aggregates are better protected from environmental stresses such as solar UV radiation [3]. It was suggested that external stress factors might lead to the activation of certain genes that help the organism's adaptation to the changing conditions by altering surface characteristics of the organism and increasing EPS (extracellular polymeric substances) production [21].…”
Section: Introductionmentioning
confidence: 99%